Cardiorespiratory performance of female and male triathletes tested by cycle ergometry and a special triathlon-triple-test - Henne, C.; Keller, H.; Rüb, M.; Nowacki, P. E. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Most studies dealing with triathlon have looked at male triathletes. The purpose of this study was to investigate the endurance performance of 11 female (25±3yrs., 58±7kg, 167±7cm) and 17 male (30±7yrs., 76±7 kg, 184±7cm), very well-trained triathletes who completed a maximal cycle ergometer test and a special developed Triathlon-Triple-Test. Methods: 1) Graded maximal cycle ergometry: 1 W/kg bw method (Nowacki 1974); performance indices: heart rate, blood pressure, gas exchange and blood lactate. 2) Triathlon-Triple-Test: gas exchange measurements during the cycling and running part; heart rate, blood pressure and blood lactate measurements during the whole test. The steady state results for heart rate (% peak HR) and oxygen uptake (% peak VO2) of each part of the Triple-Test were compared to peak heart rate (peak HR) and peak oxygen uptake (peak VO2) reached in the maximal cycle ergometer test. Additionally, percent peak HR and % peak VO2 during swimming, cycling on the athletes own bicycles under "simulating road conditions" and running on a treadmill were compared. Findings: Cycle ergometry: Mean peak HR was higher in the female (186/min) than in the male group (176/min). Mean peak VO2 was 57.9 ml/kg/min for the women, 60.1 ml/kg/min for the men. Triple-Test: During swimming the female triathletes reached 90-100 % peak HR, the male athletes only 80-90 % peak HR. During cycling and running the results were very similar for both groups with 90-95 % peak HR (cycling) and 97 % peak HR (running). Our main findings were the results regarding %peak VO2 during cycling. The women completed this part with just 60% peak VO2, the men with 74%. During running these differences were getting smaller. These results show that the cycling performance level in spite of similar % peak HR is clearly lower in our female triathletes compared to the male control group. Our results go in line with other studies (i.e. O`Toole et al. 1989) showing a high correlation of cycling economy and peak VO2 during cycling to finish time in cyclists and triathletes. Based on this a major goal for female triathletes should be the improvement of their cycling performance in order to improve their competition performance ability.